2006
DOI: 10.1542/peds.2005-0144
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of End-of-Life Care in the Pediatric Intensive Care Unit: Parents' Priorities and Recommendations

Abstract: Parental priorities and recommendations offer simple yet compelling guidance to improve pediatric end-of-life clinical practice and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
385
0
47

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(448 citation statements)
references
References 58 publications
16
385
0
47
Order By: Relevance
“…Parents wanted to receive honest information about their infant's condition and prognosis, even if the news was not good, which is similar to previous research. 11,13,14,23 They wanted to be involved in decision-making for their infant, and wanted their decisions to be respected by medical staff. If parents felt involved in the decision-making for their infant, they appeared to have a more positive perception of their infant's end-of-life care, regardless of how long their infant lived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents wanted to receive honest information about their infant's condition and prognosis, even if the news was not good, which is similar to previous research. 11,13,14,23 They wanted to be involved in decision-making for their infant, and wanted their decisions to be respected by medical staff. If parents felt involved in the decision-making for their infant, they appeared to have a more positive perception of their infant's end-of-life care, regardless of how long their infant lived.…”
Section: Discussionmentioning
confidence: 99%
“…10 These data suggest that palliative care consultation may enhance the end-of-life care for newborns, but there are still questions about what constitutes an excellent end-of-life care. Although several studies have asked the parents of children who have died about their perspectives on their child's end-of-life care, 11,12,13 these studies were not specific to parents who had lost an infant. One study that did ask parents who had an infant die in a neonatal intensive care unit 14 found that parents wanted clear information about their child's condition, and wanted to be involved in decisions that were made about their child's care.…”
Section: Introductionmentioning
confidence: 99%
“…Actor-family members used statements to ensure that they correctly understood the information provided, such as recapping what the practitioners had said and paraphrasing, more frequently than practitioners. Previous studies have found that clarity and honesty of information is of pivotal importance for families in pediatric 17,22 and neonatal intensive care settings, 23 and is associated with higher parent ratings of the quality of care. Unfortunately, information regarding patient's diagnosis, treatment and prognosis is often not communicated effectively to family members in ICU 24 and NICU.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is especially meaningful because integration of psychosocial aspects of care and the opportunity for parents to express their opinion and understand information have been highly valued by parents. 15,22,29 Wolfe et al 30 reported that the inclusion of psychosocial professionals in pediatric oncology family meetings was associated with greater concordance in the timing of physicians' and parents' understanding that the child had no realistic chance for cure, and also with greater integration of palliative care. Further studies may be valuable to determine whether the unique communication contributions of social workers and chaplains highlighted here, such as asking psychosocial questions, eliciting the family perspective, and engaging in positive talk, enhance patient and family outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1). The rationale for excluding parents of children who had died was the assumption that other research methods would be more appropriate for this group [18][19][20]. In the eventuality of transferral from one to another PICU, the parents' opinion was sought for the first admission only.…”
Section: Participantsmentioning
confidence: 99%